Mandatory appearances of forensic examiner for cross-examination in court and related systemic improvement under china's criminal procedure - Jianye Qu; Min Guo (Wolters Kluwer Medknow Publications, 2017)
In China's criminal procedure system, forensic advice is one of the key types of evidence. These advices play an important part in discovering the facts of a case, convictions, and sentencing, and they cannot be ignored in assessments of guilt and the death penalty. However, due to broad and flexible criminal laws, in actual litigation, the nonappearance of forensic examiner or mere provision of documentation of advice read in court has become the norm. This has led to the existence in name only of cross-examination rights, which directly damages the legitimate rights and interests of the parties and the objective and impartial rulings of referees. At present, there is no legal clarity in criminal proceedings that examiner should or should not be examined in court. In my opinion, the entire court system should require an appearance in court, which must be a clear mandatory appearance with specific exceptions. The system should guarantee the forensic examiner' mandatory appearances, which would inevitably improve the rules of evidence.